2016
DOI: 10.4049/jimmunol.1501565
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of DNase Preparations Confounds Analysis of the Role of DNA in Alum-Adjuvanted Vaccines

Abstract: Aluminum salt (alum) adjuvants have been used for many years as adjuvants for human vaccines because they are safe and effective. In spite of its widespread use, the means by which alum acts as an adjuvant remains poorly understood. Recently, it was shown that injected alum is rapidly coated with host chromatin within mice. Experiments suggested that the host DNA in the coating chromatin contributed to alum’s adjuvant activity. Some of the experiments used commercially purchased DNase and showed that co-inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…When injected in the absence of virus infection, dsDNA from splenocytes recapitulated many but not all of the exacerbating effects of RV on asthma-related outcomes in mice, suggesting that more complex structures containing dsDNA, rather than dsDNA alone, were responsible for the full aggravating effects. This assumption was concordant with the fact that the commercially available DNase that we used degrades not only dsDNA but also DNA-associated proteins19,3033. We therefore postulated that NETs, which contain both dsDNA and proteins/peptides, were the main source of airway dsDNA elicited by RV infection.…”
Section: Discussionsupporting
confidence: 76%
“…When injected in the absence of virus infection, dsDNA from splenocytes recapitulated many but not all of the exacerbating effects of RV on asthma-related outcomes in mice, suggesting that more complex structures containing dsDNA, rather than dsDNA alone, were responsible for the full aggravating effects. This assumption was concordant with the fact that the commercially available DNase that we used degrades not only dsDNA but also DNA-associated proteins19,3033. We therefore postulated that NETs, which contain both dsDNA and proteins/peptides, were the main source of airway dsDNA elicited by RV infection.…”
Section: Discussionsupporting
confidence: 76%
“…It is difficult to evaluate the contributions of NETs since it is difficult to eliminate them entirely from injected alum. As for the accompanying chromatin, a couple of papers have suggested that host DNA may indeed increase alum’s effects but host DNA is certainly not the only intrinsic adjuvant induced by alum ([2931] but see [32]). Alum may also act simply as a particle, lysing lysosome and releasing lysosomal enzymes into the cytoplasm [3335] or by distorting the plasma membrane of antigen presenting cells [36] and/or somehow by its ability to rapidly induce production if cytokines and chemokines [37,38].…”
Section: Insoluble Salts and Other Particulate Adjuvantsmentioning
confidence: 99%
“…Some studies suggested that the release of dsDNA from damaged and dying host cells, which is induced by alum injection, may contribute to priming of Th2 CD4 + T cells (4,5) and enhance MHC class II-mediated Ag presentation, prolonging CD4 + T cell interactions with DCs (5). However, a recent report by Noges et al (6) showed that some of the DNase preparations used in the above studies are contaminated by proteases, casting doubt on the significance of dsDNA in responses to alum.…”
mentioning
confidence: 98%